Peningkatan Kepercayaan Wakif Melalui Prinsip Transparansi dan Akuntabilitas - Evrytanadha, Ayiek; Erma, Dwi (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2024)
Abstract: This research aims to analyze the concept of transparency and accountability in waqf institutions in Indonesia. This type of research is research using library research methods, namely research that utilizes library sources to obtain research data. One of the characteristics of library research is that researchers are confronted directly with text or numerical data and not direct knowledge from the field or eye-sanctions in the form of events, people or other objects. The success of waqf management lies in the existence of nadzir in maximizing the potential of waqf funds, so that the existence and quality of nadzir need to receive more attention from the government, whether the nadzir are individuals, organizations and legal entities. Wakif is influenced by Nadzir's professionalism in managing waqf, his expertise in managing waqf assets, waqf must refer to modern management principles. The application of the principle of accountability has increased public trust in waqf institutions. Nadzir's professionalism in waqf management is to manage waqf transparently and accountably so that wakifs participate in the development of waqf, both in reporting and otherwise. Keywords: accountability; nadhir; waqf